Midazolam Ameliorates Acute Liver Injury Induced by Carbon Tetrachloride via Enhancing Nrf2 Signaling Pathway - Zhang, Yongyan; Zhu, Yadi; Li, Ying; Ji, Feng; Ge, Guangbo; Xu, Hua (Frontiers in Pharmacology, 2022)
Oxidative stress contributes greatly to initiation and progression of liver injury. Activation of nuclear-factor erythroid 2-related factor 2 (Nrf2) has been considered as an attractive strategy for preventing and treating the oxidative damage related to liver injury. This study aimed to find an efficacious agent to activate Nrf2/HO-1 signaling pathway from clinically used therapeutic agents and to characterize the usefulness for preventing and treating CCl4 induced acute liver injury. For this purpose, a series of clinically used therapeutic agents were collected and their activation potentials on Nrf2 were assayed by using 293T-Nrf2-luc cell line. Among all tested therapeutic agents, midazolam was found with good Nrf2 activation effect and this agent could significantly ameliorate CCl4-induced damage of HepG2 cells. In vivo animal tests showed that pretreatment with midazolam reduced the liver pathological tissue damage and the serum levels of ALT and AST in CCl4-induced liver injury mice. Further investigations showed that midazolam could strongly up-regulate the expression of both Nrf2 and HO-1 in the mice liver, accompanied with increasing of the levels of antioxidant enzyme SOD and reducing the production of MDA, as well as reducing the pro-inflammatory cytokines (IL-6, TNF-α) secretion. Collectively, our results clearly demonstrate that midazolam can ameliorate CCl4-induced acute liver injury and oxidative stress via activating the Nrf2 signaling pathway.